PERAN GURU PAI DALAM MENGANTISIPASI PERILAKU PERUNDUNGAN (BULLYING) DI SMP NEGERI 01 CIPONGKOR BANDUNG BARAT - Saepulloh, Saepulloh; Mirawanti, Eris (Prodi Pendidikan Agama Islam STAI Darul Falah, 2023)
This study aims to describe the role of PAI teachers in anticipating bullying behavior, the efforts of PAI teachers in anticipating bullying behavior, and the supporting and inhibiting factors for PAI teachers’ efforts to anticipate bullying behavior at SMP Negeri 01 Cipongkor. To achieve the above objectives, this research uses phenomenological and qualitative research methods. The data collection techniques used are observation, interviews, and documentation. Data is analyzed by reducing data, presenting data, and drawing conclusions. The results of this study indicate that the role of PAI teachers in anticipating bullying behavior at SMP Negeri 01 Cipongkor is as educators, facilitators, role models, motivators, mentors, and evaluators. Efforts made by PAI teachers in anticipating bullying behavior at SMP Negeri 01 Cipongkor, namely, providing an understanding of bullying to students, maximizing learning, holding anti-bullying programs, making policies regarding bullying actions, providing supervision, appeals, and advice to students, there is communication that is open to reporting cases of bullying. Supporting factors for the implementation of PAI teacher efforts are a safe and comfortable school environment for students, supporting facilities or infrastructure, and good cooperation between all parties. The inhibiting factors for the efforts of PAI teachers are the different absorption capacities of students, problematic families, and poor friendship environments.